STRATEGIES IN SIMULTANEOUS INTERPRETING - Shokirov Manuchekhr Shamsidinovich (TADQIQOTLAR, 2025)
Abstract:  Simultaneous  interpreting  involves  listening  to  a  speaker  in  one language  and  interpreting  their  words  into  another  language  in  real-time.  This demanding  task  requires  the  interpreter  to  process  information  rapidly  while simultaneously speaking, making it one of the most challenging forms of language translation.  Here  are  some  examples  of  cognitive  demands  in  simultaneous interpreting: